The Development of Selective Attention Orienting is an Agent of Change in Learning and Memory Efficacy - Markant, Julie (Infancy, 2015)
The present study examined whether the developmental transition from facilitation-based orienting mechanisms available very early in life to selective attention orienting (e.g., inhibition of return, IOR) promotes better learning and memory in infancy. We tested a single age group (4-month-olds) undergoing rapid development of attention orienting mechanisms. Infants completed a spatial cueing task designed to elicit IOR, in which cat or dog category exemplars consistently appeared in either the cued or noncued locations. Infants were subsequently tested on a visual paired comparison of exemplars from these cued and noncued animal categories. As expected, infants showed either facilitation-based orienting or the more mature IOR-based orienting during spatial cueing/encoding. Infants who demonstrated IOR-based orienting showed memory for both specific exemplars and broader category learning, whereas those who showed facilitation-based orienting showed weaker evidence of learning. Attention orienting also interacted with previous pet experience, such that the number of pets at home influenced learning only when infants engaged facilitation-based orienting during encoding. Learning in the context of IOR-based orienting was stable regardless of pet experience, suggesting that selective attention serves as an online learning mechanism during visual exploration that is less sensitive to prior experience.